Non-destructive Thermal Monitoring of Temperature and Flow Rate of the Heat Carrier in a Heating Device - Pavlov, Mikhail Vasilyevich; Karpov, Denis Fedorovich; Vafaeva, Khristina Maksudovna; Reddy, G. Keerthi; Makhija, Himanshu; Deorari, Rajesh; Verma, Raman; Raju, K. Butchi; Tiwari, Deepak Kumar (E3S web of conferences, 2024)
Conducting various calculations for the heating system of a building under operational conditions is impossible without knowledge of the temperature and flow rate of the heat carrier at specific points. Contact measurement means are not always applicable, especially for small-diameter pipelines. Measurement techniques based on the theory of non-destructive thermal inspection allow for remote and timely acquisition of all necessary information. The object of the study is the floor node of the building's heating system. The subject of the study is the temperature and flow rate of the heat carrier passing through the heating device. The research aim is to determine the temperature and flow rate of the heat carrier passing through the heating device under operational conditions. The research method involves the theory of non-destructive thermal inspection, as well as heat balance and heat transfer equations for a vertical flat wall. Research findings reveal that during thermovisual inspection, the temperature of the heat carrier in the supply and return pipelines of the floor node respectively amounted to 51.6 ℃ and 49.6 ℃. The flow rate of the heat carrier through the heating device model MS-140M2-500, with a heat transfer coefficient of 8.5 W/(m²⋅K), was determined to be 195.0 kg/h. Recommendations include utilizing a thermal imager with an absolute measurement error not exceeding ±0.15 ℃ for determining the flow rate of the heat carrier through the heating device. The influence of measurement error of indoor air temperature on the accuracy of determining the heat carrier flow rate is insignificant (not exceeding ±2%). The relative error in determining the heat transfer coefficient of the heating device does not exceed ±1%.